The Ciceronian Auto-apotheosesin Skelton's Garlande of Laurell. - CARLSON, DAVID RICHARD (Philological Quarterly)
The article explores John Skelton's Garlande of Laurell, showing how the Tudor poet engages with Cicero's self-praising epic tradition while simultaneously subverting it. Topics include Cicero's auto-apotheotic epics (De consulatu suo and De temporibus suis), the divine apparatus and heroic self-presentation in Ciceronian poetry, Skelton's extensive self-quotation and autobibliography, and how Skelton's poem both invokes and mocks the desire for immortality and fame exemplified by Cicero.